Penilaian Kinerja Sarana Dan Prasarana Daerah Irigasi (DI) Desa Muara Jalai Kabupaten Kampar - Yulasni Astri; Manyuk Fauzi; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Rice production in Indonesia is affected one of which is infrastructure of irrigation. Irrigation area that was built require Operations and Maintenance in order to function properly. This study aims to evaluate the performance of operation and maintenance on Muara Jalai irrigation system. Some indicators based of Permen PU No.12/PRT/M/2015 was used to determine the performance of the irrigation system such as physical infrastructure, plant productivity, supporting facilities, personnel organization, documentation and water user association (P3A). This result showed that total intex of performance of irrigation system on Muara Jalai is 63,65%. This result classified for bad category and need attantion.Keywords : Operations and Maintenance, irrigation system performance, Permen PU No.12/PRT/M/2015